Theories of consciousness : an introduction and assessment - Seager, William (Routledge, 1999)
The most remarkable fact about the universe is that certain parts of it are conscious. Somehow nature has managed to pull the rabbit of experience out of a hat made of mere matter. Making its own contribution to the current, lively debate about the nature of consciousness, Theories of Consciousness introduces variety of approaches to consciousness and explores to what extent scientific understanding of consciousness is possible. Including discussion of key figures, such as Descartes, Foder, Dennett and Chalmers, the book covers identity theories, representational theories, intentionality, externalism, and the new information-based theories.